Endoscopic findings and lesion distribution in amebic colitis. Issue 6 (June 2015) - Horiki, Noriyuki; Furukawa, Keiichi; Kitade, Takashi; Sakuno, Takashi; Katsurahara, Masaki; Harada, Tetsuro; Tano, Shunsuke; Yamada, Reiko; Hamada, Yasuhiko; Inoue, Hiroyuki; Tanaka, Kyosuke; Gabazza, Esteban C.; et al.
Abstract: A retrospective cohort study was conducted in 55 symptomatic patients with amebic colitis that visited at St. Luke's International Hospital and Mie University Hospital from 1994 through 2013. To diagnose amebic colitis, 40 patients underwent total colonoscopy within 1 week after hospital visiting and before receiving any treatment. The percentage of characteristic endoscopic findings of amebic colitis including discrete ulcers or erosions with white or yellow exudates were 0% in terminal ileum, 93% in cecum, 28% in ascending, 25% in transverse, 15% in descending, 20% in sigmoid colon and 45% in rectum. The rectal lesions in 55% of patients with amebic colitis were nonspecific. The trophozoite identification rate by direct smear of intestinal tract washings performed during colonoscopy was 88%. The protozoan identification rate was 70% in biopsy specimens taken from the periphery of the characteristic discrete ulcers. Total colonoscopy should be considered for the diagnosis of amebic colitis.